A CRISPR-Cas9 delivery system for in vivo screening of genes in the immune system - LaFleur, Martin W.; Nguyen, Thao H.; Coxe, Matthew A.; Yates, Kathleen B.; Trombley, Justin D.; Weiss, Sarah A.; Brown, Flavian D.; Gillis, Jacob E.; Coxe, Daniel J.; Doench, John G.; Haining, W. Nicholas; Sharpe, Arlene H. (Nature communications, 2019)
Therapies that target the function of immune cells have significant clinical efficacy in diseases such as cancer and autoimmunity. Although functional genomics has accelerated therapeutic target discovery in cancer, its use in primary immune cells is limited because vector delivery is inefficient and can perturb cell states. Here we describe CHIME: CHimeric IMmune Editing, a CRISPR-Cas9 bone marrow delivery system to rapidly evaluate gene function in innate and adaptive immune cells in vivo without ex vivo manipulation of these mature lineages. This approach enables efficient deletion of genes of interest in major immune lineages without altering their development or function. We use this approach to perform an in vivo pooled genetic screen and identify Ptpn2 as a negative regulator of CD8 + T cell-mediated responses to LCMV Clone 13 viral infection. These findings indicate that this genetic platform can enable rapid target discovery through pooled screening in immune cells in vivo. The use of functional genomics in primary immune cells has been limited by inefficient vector delivery and risk of perturbing cell states. Here the authors present CHimeric IMmune Editing (CHIME) for in vivo evaluation of gene function and pooled screening approaches.